1993
DOI: 10.1007/bf00042287
|View full text |Cite
|
Sign up to set email alerts
|

Restoring adventitious shoot formation on chrysanthemum leaf explants following cocultivation with Agrobacterium tumefaciens

Abstract: Explants from leaves of in vitro-grown chrysanthemum (Dendranthema grandiflora Tzvel.) cultivars regenerated adventitious shoots without an intermediate callus phase. Puncturing explants with a brush increased regenerations, but in combination with cocultivation with Agrobacterium tumefaciens it had an adverse effect on shoot formation. The negative effect of brushing and cocultivation could be overcome by preculturing explants for 8 days. Preculture altered the location of transformed sites but did not inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…A similar reduction in regeneration due to extensive exposure of the wound sites to Agrobacterium has been observed in other species, e.g. potato (De Block 1988) and chrysanthemum (De Jong et al 1993). Therefore, a 2-to 3-day co-cultivation period without pre-incubation was adopted as the standard transformation procedure.…”
Section: Optimization Of Transient Expressionsupporting
confidence: 75%
“…A similar reduction in regeneration due to extensive exposure of the wound sites to Agrobacterium has been observed in other species, e.g. potato (De Block 1988) and chrysanthemum (De Jong et al 1993). Therefore, a 2-to 3-day co-cultivation period without pre-incubation was adopted as the standard transformation procedure.…”
Section: Optimization Of Transient Expressionsupporting
confidence: 75%
“…e timing of Agrobacterium infection is considered an important factor for raising the infection e ciency, resulting in increased plant transformation e ciency (De Jong et al 1993;Shinoyama et al 2002a; Teixeira da Silva and Fukai 2002a). Shinoyama et al (1998) demonstrated that the Agrobacterium culture in the logarithmic growth phase confers high infectability on plants and that the number of transformed cells increases when using the Agrobacterium in this phase.…”
Section: Explants For Infection and Its Treatmentmentioning
confidence: 99%
“…Because both Agrobacterium-mediated transformation and shoot regeneration are promoted by wounding the explants (De Jong et al 1993), Shinoyama et al (1998) compared the di erence in transformation frequencies with the two leaf-cutting methods using scalpels or corkborers. More Agrobacterium-infected cells were obtained from the segments cut with cork-borers than from those cut with scalpels.…”
Section: Explants For Infection and Its Treatmentmentioning
confidence: 99%
“…but the efficiency of gene transfer is very cultivar specific (Van Wordragen et al 1991;Bush and Pueppke 1991). In addition, the conditions required for successful regeneration of plants via direct organogenesis or somatic embryogenesis are also specific to individual cultivars (May and Trigiano 1991;De Jong et al 1993;Lowe et al 1993;Pavingerova et al 1994). Explant type and the incubation medium can strongly influence the number of adventitious shoots produced within cultivars.…”
Section: Biotechnologymentioning
confidence: 99%